Anomali Penderitaan Orang Percaya: Suatu Analisis Makna Penderitaan Berdasarkan Filipi 1:27-29 - Djone Georges Nicolas (CV. Syntax Corporation Indonesia, 2021)
The suffering of those who have believed in Jesus Christ as Lord and Savior, served God's work and continued to try to live a godly life, is seen by some believers as an anomaly. The aim of this research is to find out whether the suffering of believers is an anomaly or is it natural. How believers suffer should be viewed based on Philippians 1: 27-29. This research uses descriptive qualitative research, with a literature analysis method approach and narrative interpretation, by collecting data through biblical sources, books, journals, digital articles, interviews and other documents related to the issues being studied. First, suffering for believers is not an option but a necessity because suffering is package with faith. Second, suffering for believers is part of the struggle for faith. Third, suffering for believers is a gift from God to be grateful for and enjoy. In conclusion, even though suffering is unpleasant, every believer must accept it as part of God's calling. Because Jesus Christ himself did not call anyone by giving the sweet promise of life without problems, but has confirmed that anyone who wants to follow Him is obliged to carry the cross which is identical with suffering.